Determination of concentrations of pollutant gases and trace elements in air of holy city of Karbala - Adnan R. Mahdi; Kasim K. Alasedi (Al-Qadisiyah Journal of Pure Science, 2017)
For the period of time , December 2012 – February 2013 a study has been taken aplace to detarmine deconcentration of pollutants in the air of the holy city of karbala that included the following gases ( H2S , CO , NH3 , NO , NO2 , SO2 , SiH4 , O3 ) and the total concentration of hanged particle in the air on two hights ( 1.5m),( 3 m ) and the concentration of some trace elements specially( Zn , Cr , Cd , Co , Mn , Fe , Pb , Cu ) in the Soil and Leafs where the study was conducted .The Flame Atomic Absorption was used to measure the concentration , these measured concentrationswas compared with the National and World Standards to determined which places were polluted and to suggest the suitable solutions for ( 10 ) traffic stations in the city where the samples were taken under aspecific climate measurment .The results of the study shows a clear rise in the average concentrations of gases and a high rise in the Concentrations of the hanged particles in all places . The study was condacted when a huge number of pilligrims arrived to the city . Then it is a must to find the appropriate steps and solutions to treat the air pollution in the holy city .